Social Functioning of Kratom (Mitragyna speciosa) Users in Malaysia - Singh, Darshan; Müller, Christian P.; Vicknasingam, Balasingam K.; Mansor, Sharif M. (Journal of Psychoactive Drugs, 2015)
Kratom (Mitragyna speciosa) is an indigenous plant known for its traditional medicinal use, and for its addiction potential, in Southeast Asia. In recent years, kratom and its major alkaloid, mitragynine, spread worldwide with largely unknown effects on behavior and mental health. Recent studies show that kratom use can lead to dependence and that mitragynine works as an addictive drug in animal studies. Nevertheless, kratom preparations were also suggested as a less harmful substitute in opiate withdrawal. Potential side-effects of prolonged kratom use, however, are currently unclear. The aim of this study was to investigate the social functioning of regular kratom users in Malaysia. A cross-sectional survey was carried out in three northern states of Peninsular Malaysia investigating 293 regular kratom consumers using the Addiction Severity Index in a snowball sampling technique. Findings showed that regular kratom users do not experience major impairments in their social functioning, despite being dependent on kratom for prolonged periods. Our findings suggest that chronic kratom administration does not significantly impair social functioning of users in a natural context in Malaysia.
EVALuna2:23727